Community health workers' counseling is based on a deficit model of behavior change. - Micah B Goldwater; Faiz A Hashmi; Sudipta Mondal; Cristine H Legare (PLOS Global Public Health)
In 2005, India launched the Accredited Social Health Activist (ASHA) program, which has augmented access to medical services and health education in marginalized rural communities. Despite notable progress in health delivery, uptake of medical services remains below target levels. The current research asked ASHAs and their clients why people reject medical advice and what the ASHAs could do to convince them otherwise. Our results identify a consistent mismatch between reasons to reject advice versus how to persuade clients to follow the advice. Two reasons were primarily cited for rejecting the uptake of medical services: insufficient or inaccurate understanding of the medical benefits of these services and the dynamics of the social situation, such as pressure from family members. In contrast, the predominant solutions addressed these knowledge gaps; ASHAs and their clients felt that highlighting the health advantages would be the most effective persuasion technique. ASHAs and their clients infrequently mentioned strategies addressing societal dynamics and norms. This mismatch between barriers to uptake and solutions suggests that the ASHA program inadvertently operates with a "deficit model" of decision-making and persuasion. The deficit model is the belief that the way to convince people to comply with health recommendations is to address their knowledge deficit by educating them on the medical benefits. The current research suggests that ASHAs should be trained in the science of belief revision and behavior change, which requires directly addressing the concerns and motivations of others, not just providing information.